Scaling Behaviour, Optical and Photoluminescence Properties of La2Hf2O Films with Annealing Treatments. (October 2019) - Li, Z; Ma, C Y; Zhang, Q Y
Abstract: The structure, optical and PL characteristics of La2 Hf2 O7 (LHO) films deposited by rf sputtering and subsequently annealed at 800-950°C are studied by x-ray diffraction (XRD), atomic force microscopy (AFM), UV/VIS spectrophotometry, and photoluminescence (PL) measurements. Structural studies indicate that LHO films with 37% atomic ratio of La/(La+Hf) have shown high crystallization temperature higher than 900°C. The scaling behaviors of AFM topographical profiles were analysed using one-dimensional power spectral density analysis (1DPSD). For as-grown films, only one growth exponent α is evidenced. For annealed films two different slopes α 1 and α 2 were observed, indicating distinct growth dynamic in LHO films. The estimated optical band gap was found to be in the range of 5.18-5.55 eV. Photoluminescence (PL) spectra of LHO films in visible light range (i.e., at 412 435 nm and 468 nm, respectively) can be attributed to localized states at the band tails and oxygen vacancies, respectively. This PL can be diminished or decreased by adjusting structural properties i.e. the amount of oxygen vacancies or some other kind of structure defects in the films by thermal annealing processing.